Evaluation of cardiovascular risk in patients with rheumatoid arthritis. (29th March 2019) - Parrão, Madalena; Soares, Susana; Salema-Oom, Madalena; Fernandes, Rita; Cardoso, Alexandra; Vaz Patto, José
Abstract : Introduction: Rheumatoid Arthritis (RA) and fibromyalgia (FM) are among the most prevalent rheumatic diseases in women causing significant functional and occupational disability [1 ]. FM main feature is diffuse and widespread musculoskeletal pain while RA is characterized by chronic inflammation, preferably of peripheral joints, which may lead to the appearance of deformities. In Portugal, RA affects between 0.8 to 1.5% of the population [1 ], mainly postmenopausal women, and cardiovascular diseases (CVD) have been identified as the main cause of death, in which the role of atherosclerosis is recognized as determinant. In clinical practice, according to the European League Against Rheumatism recommendations, the Systemic Coronary Risk Evaluation (SCORE) index is the best tool to quantify that risk in RA patients, having no specific guidelines for it [2 ]. SCORE index estimates the risk of an individual having the first fatal cardiovascular event within 10 years, whether would be a heart attack, stroke or other occlusive artery disease, including cardiac death. This work aimed to assess the 10-year CVD risk in patients with RA using the SCORE predictive index and its comparison with fibromyalgia patients. Material and methods: The sample was selected by convenience, including all female patients with RA and FM with recent data on blood lipid levels, assisted in outpatient or inpatient settings. Patients with clinical analysis performed for more than one year and/or patients with fibromyalgia and other associated rheumatic diseases of inflammatory nature were excluded. Several factors as age, rheumatic and other conditions, smoking habits, and type and frequency of physical activity were recorded. Blood pressure, anthropometric and body composition, analyzed with InBody 720, were used to calculate the high risk SCORE index. Data was studied using the rheumatic pathology as the dependent variable. Results: A total of 40 women, 24 with RA and 16 with FM, aged 33 to 89 were included. The mean age was 64 ± 11 years for RA patients and 60 ± 8 years for FM patients and the prevalence of comorbidities was similar in both groups ( p  > 0.05). The mean SCORE index value for RA patients was 2.5 ± 1.4 higher than the 1.7 ± 0.8 found for FM patients. By using the SCORE index, the subjects were divided into 3 risk categories and although the majority (80 %) was classified as of moderate risk, two patients (5%) were identified as at high risk of fatal cardiovascular event in 10 years. Discussion and conclusion : The application of the SCORE index showed a higher 10-year risk of fatal CVD for RA patients compared to FM patients although not significant.